口 : understanding the Chinese character of mouth and beyond. - Hung, Yi-Sheng. (2011)
Chinese characters are one of the oldest living written form with a history dating back to 5000 years. I am particularly interested in the character of mouth (口 kou), which is one of the common root (radical) elements in Chinese characters. They are used in various Chinese characters that are used to describe sound, action, emotion, people, and other important Chinese concepts. The aim of this project is to better understand the meaning of these characters through reading into its history and development, and also emphasise on how certain characters with the mouth radical can be better appreciated through application in the context of a fine dining restaurant.